Batch Scheduling Model in Job Shop with Heterogeneous Group Machine to Minimizing Actual Flow Time - RIZVIYATMAJA SARIAN (NIM 23405003), FEDO
This Research develop batch scheduling model in Job Shop with heterogeneous group machine. A group of machine called heterogeneous if machines can produce same output, but at least one machine have different specification, like: operation, setup time or processing time. The criteria for developed batch scheduling model is minimizing total actual flow time, which defined as the time the job spent in shop from the starting time of the processing until due date. Decision variables in this research are total batch, size batch, and batch sequence. There are 2 Algorithm that suggested getting the solution of model, Optimal Batch Scheduling Algorithm and Sub-Optimal Batch Scheduling Algorithm. The output of experiment indicates that model can resolve batch scheduling problem with heterogeneous group machine. From the output show that batch with same part not always scheduled in succession and the size of batch not always equal.